Psycho Education with a Solution Focused Brief Therapy Approach to Improve Subjective Well-Being Long-distance Marriage - Dedy Kurniadi; Firman Firman; Netrawati Netrawati (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2023)
The aim of this study was to evaluate the use of a modeling strategy in conjunction with the SFBT method to improve marital ties. There is no clear statistical data regarding the number of couples who carry out long-distance marriages in Indonesia. This writing is done through a library approach. Learning occurs through imitation, not only by imitating but also by adding or removing behaviors, such as concentration while studying, and the SFBT modeling techniques and approaches are the result of this procedure. Sources of data in this study were obtained from books, national and international articles. The data that has been obtained will be analyzed using descriptive analysis methods. The focus of this research includes: 1) How is the scope and purpose of SFBT counseling in an effort to overcome students who have difficulty concentrating on learning; 2) What is the procedure for handling SFBT counseling in dealing with students who have difficulty concentrating on studying; 3) How effective is the application of SFBT counseling in an effort to deal with students who have difficulty concentrating on learning. This study shows the results that SFBT counseling is the most common and effective counseling therapy and is often used to overcome the problem of students' lack of concentration in learning at the elementary, junior high, high school/vocational school, and university levels.